Níveis energéticos e proteicos sobre o desempenho, crescimento e viabilidade econômico-financeira de Ovinos somalis brasileira em confinamento - Alves, Francisco Gleyson da Silveira (2019)
The objective in the present study was to evaluate the intake, nutrient digestibility coefficient, nitrogen compounds balance, ruminal and blood parameters, growth curve and economic-financial viability of Brazilian Somalis sheep submitted to diets with different dietary levels in confinement. Four experimental trials were performed. In the first trial a completely randomized design was adopted in a 3x2 factorial arrangement, with three ratios of total digestible nutrients (TDN) and crude protein (CP) (TDN:CP 422:70; 643:102 and 763:120) and two sexes (12 non-castrated male (15.40±3.21 kg) and 12 female (14.86±2.50 kg)). The sheep fed the diet TDN:CP 763:120 presented lower intake of dry matter (DM), organic matter (OM), CP, ether extract (EE), total carbohydrates (TC), non-fibrous carbohydrates (NFC) and TDN, lower digestibility of MS. OM, CP AND EE, and lower ingested nitrogen (IN), fecal nitrogen (FN) and excreted nitrogen (EXN). A significant effect of the interaction was observed on urinary nitrogen (UN) and on the ratios RN/IN, UN/IN and EXN/IN. Regardless of the sex, dietary energy and protein levels influenced the variables evaluated. In the second trial, a completely randomized design was adopted in a 3x2 factorial arrangement, with three diets (TDN:CP 524:75; 668:81 and 781:95) and two sexes (10 non-castrated male (26.68±5.79 kg) and 11 female (24.98±4.45 kg)). Higher intakes of DM, OM, CP, EE and fibrous components, higher values of IN, FN and RN besides higher consumption of microbial protein were observed for non-castrated males. Sheep fed the TDN:CP diet 781:95 presented higher nutrient digestibility, higher IN, RN, FN/IN, RN/IN and glucose and lower intake of fibrous components. Non-castrated males showed higher responses and the higher TDN:CP ration provided better results for the studied variables. In the third trial, a completely randomized design was adopted in a 2x2 factorial arrangement, with two diets (0 and 15% of reduction in TDN and CP values) and two sexes (8 non-castrated male and 8 female). The average daily weight gain and the average daily gain and dry matter intake (DMI) ratios were not influenced by the sex or diet. In the first phase, the sex did not influence the analyzed variables, and sheep fed the diet with 15% of reduction presented higher feed efficiency (FE) and lower DMI. In the second phase, the diet did not influence the evaluated variables. Non-castrated males presented higher final live weight and DMI, whereas the females presented better FE. The weight at maturity was similar, however the maturity rate differed between the sexes. The highest absolute growth rate (AGR) was observed in the animals that were fed the diet with 0% of reduction, with maximum point close to 90 days for both sexes. Regardless of sex, the 15% reduction in TDN and CP affects the maturity rate and non-castrated males presented higher AGR than females. In the fourth trial, four simulations of productive scenarios were performed considering two sex classes (8 non-castrated male (15.75±2.25 kg) and 8 female (14.91±2.12 kg)) and two diets (0 and 15% of reduction in TDN and CP levels). For both sexes, the diet with 15% of reduction presented higher net income, return rate, return internal rate, profitability index, profitability rate and lower pay back when compared to the diet with 0% of reduction. The increase in the favorability of the sale price makes the activity viable. Regardless of sexual class, the reduction of 15% in TDN and CP did not affect the economic-financial indexes.